Primary hypogonadism, partial alopecia, and Müllerian hypoplasia: report of a fifth family and review - Al‐Obaidi, Ruqayah G. Y. (Clin Case Rep, 2017)
Primary hypogonadism combined with Müllerian hypoplasia and partial alopecia are common features of this syndrome, which was reported only in four earlier families from areas where consanguineous marriage is prevalent. An autosomal recessive pattern of inheritance was suggested earlier and is supported by this report.